Women Empowerment and Gender Equality: Catalyst for a Progressive India - Nadar, Jancy Ramesh (Journal of Neonatal Surgery, 2025)
India is progressing toward inclusive development, with gender equality and women’s empowerment playing a vital role. Despite legal and policy advancements, women continue to face challenges such as gender bias, wage inequality, limited decision-making power, and low awareness of government schemes. This study uses a descriptive, mixed-method approach with simulated data from students, educators, and working women. Findings identify education as a key driver of empowerment, though its impact is constrained by structural inequalities. Economic and social barriers persist, restricting women’s full participation. The study concludes that achieving true gender equality requires systemic reforms in education, policy implementation, and societal attitudes.